Current Trends in Carotid Artery Revascularization - Crawford, Emily B.; Secemsky, Eric A. (Seminars in Interventional Radiology, 2025)
Carotid artery revascularization plays an important role in stroke prevention among patients with carotid stenosis. While carotid endarterectomy has been the mainstay of revascularization in those with moderate to severe stenosis, the evolution of carotid artery stenting and the recent expansion of Medicare coverage have impacted utilization trends and guideline recommendations. We aim to review currently available data on revascularization techniques, discuss important factors influencing treatment decisions, and explore future directions of carotid stenosis management.
Keywords: carotid artery stenosis; carotid revascularization; carotid endarterectomy; carotid artery stenting